A case report of a severe fluoropyrimidine-related toxicity due to an uncommon DPYD variant - De Falco, Vincenzo (Medicine (Baltimore), 2019)
INTRODUCTION: Fluoropyrimidines such as 5-fluorouracil (5-FU) and its orally active prodrug, capecitabine, are widely used in the treatment of gastrointestinal cancer, including colorectal cancer. Dihydropyrimidine dehydrogenase (DPD) plays an important role in the 5-FU metabolism. Dihydropyrimidine dehydrogenase gene (DPYD) is a highly polymorphic gene with several hundreds of reported genetic variants and DPD activity levels vary considerably among individuals, with different 5-FU-related efficacy and toxicity. About 5% of the population is deficient in DPD enzyme activity. The most well studied DPYD variant is the IVS14+1G>A, also known as DPYD ∗2A. In this report, we present a case of a patient with a double heterozygote DPYD variant (DPYD activity score: 0,5 according to Clinical Pharmacogenetics Implementation Consortium) who experienced a severe fluoropyrimidine-related toxicity resolved without any consequence. PATIENT CONCERNS: A 46-years-old Caucasian man with diagnosis of left colon adenocarcinoma underwent left hemicolectomy on July 2017: pT3 G3 N1c M0. According to the disease stage, he started an adjuvant therapy with XELOX using capecitabine at 50% of total dose, because of his DPYD IVS14+1G>A variant, detected before the treatment. DIAGNOSIS: After few days, despite of this dose reduction, he experienced life-threatening adverse events such as mucositis G3, diarrhea G3, neutropenia G4, thrombocytopenia G4, and hyperbilirubinemia G3 according to Common Terminology Criteria for Adverse Events v 5.0. INTERVENTIONS: As first, we set up an intensive rehydration therapy, antibiotic and antifungal prophylaxis, Granulocyte-Colony Stimulating Factors, and supportive blood transfusions. Additional genetic tests revealed a double heterozygote variant of DPYD gene (DPYD IVS14+1G>A and 2846A>T) which is a very rare situation and only 3 cases are described in literature, all of them concluded with patient's death. OUTCOMES: After 3 weeks of intensive therapy, the patient was fully recovered. Furthermore, all the whole-body CT scans performed since discharge from the hospital until now, have confirmed no evidence of disease. CONCLUSIONS: Recent studies demonstrated that screening strategy for the most common DPYD variants allowed for avoiding toxicities and saving money. This report underlines the importance of genotyping DPYD before treatment and emphasizes the role of genotype-guided dose individualization.